Recent Advances in the Development of Near-Infrared Fluorescent Probes for the in Vivo Brain Imaging of Amyloid-β Species in Alzheimer’s Disease - Bajad N.G.; Kumar A.; Singh S.K. (My University, 2025)
The deposition of β-amyloid (Aβ) plaques in the parenchymal and cortical regions of the brain of Alzheimer’s disease (AD) patients is considered the foremost pathological hallmark of the disease. The early diagnosis of AD is paramount in order to effective management and treatment of the disease. Developing near-infrared fluorescence (NIRF) probes targeting Aβ species is a potential and attractive approach suitable for the early and timely diagnosis of AD. The advantages of the NIRF probes over other tools include real-time detection, higher sensitivity, resolution, comparatively inexpensive experimental setup, and noninvasive nature. Currently, enormous progress is being observed in the development of NIRF probes for the in vivo imaging of Aβ species. Several strategies, i.e., the classical push-pull approach, “turn-on” effect, aggregation-induced emission (AIE), and resonance energy transfer (RET), have been exploited for development. We have outlined and discussed the recently emerged NIRF probes with different design strategies targeting Aβ species for ex vivo and in vivo imaging. We believe that understanding the recent development enables the prospect of the rational design of probes and will pave the way for developing future novel probes for early diagnosis of AD. © 2023 American Chemical Society.